PERCEIVED VALUE AND TRUST TOWARDS PATIENT LOYALTY: A LITERATURE REVIEW - Salsabila Az Zahra; Naili Farida; Septo Pawelas Arso (Medical Technology and Public Health Journal, 2022)
Increasing patient loyalty through patient-provider relationships becomes the key factor in medical providers’ successes. Perceived value is the long-term value that customers provide to hospitals. The creation of added value for customers, and increasing the level of satisfaction will make a major contribution to the possibility of customers staying, and customers are increasingly valuable to service providers. This study explored the mediated relationship between patients’ perceived value, trust, and patient loyalty. This study aims to examine the perceived value and trust in patient loyalty both in hospitals and medical centers. This literature review study was searched from 3 databases, namely PubMed, Scopus, and Google Scholar published between January 1, 2018-May 31, 2022. Inclusion criteria were research on medical care loyalty, experience in the patient's perceived value of hospital services, and patient’s trust in the hospital. A total of 11 from 86 articles found were selected for review. Based on 11 articles that have been reviewed discussing customer value and trust in patient loyalty. Hospital and Medical Center as health provider has a relationship between patients’ perceived value of medical services, commitment to the patient-provider relationship, and patient loyalty. Furthermore, when the patient demonstrated higher levels of trust in a healthcare provider, the relationship of perceived value, commitment, and patient loyalty was also enhanced.